Dietary Fibres in Processed Meat: A Review on Nutritional Enhancement, Technological Effects, Sensory Implications and Consumer Perception - Marius-Mihai Ciobanu; Diana-Remina Manoliu; Mihai Cătălin Ciobotaru; Elena-Iuliana Flocea; Paul-Corneliu Boișteanu (Foods)
Meat is an essential source of nutrients in the human diet and a component of global food security. In the context of a growing demand for functional and healthy foods, the addition of non-meat ingredients, such as dietary fibres, is a promising strategy for improving the quality of meat products. This review aimed to identify and synthesise the available recent literature regarding the impact of fibre-rich ingredients on the properties of meat products, investigating how various plant sources (such as cereals, vegetables, legumes, and fruits) can be used in various forms of meat products, such as meat pastes, emulsified products, and minced and restructured meat products. Analyses of technological parameters revealed improvements in water-holding capacity, cooking losses, and an increased production yield. The addition of fibre has demonstrated a favourable effect on low-fat products, stabilising the emulsion and improving its physical texture properties. The chemical analysis highlighted an increase in dietary fibre and mineral content, as well as a decrease in fat content depending on the type and level of fibre added. Sensory changes included aspects related to the colour, aroma, texture, and overall acceptability of the products. The optimisation of the type and level of fibre is essential to obtain meat products with improved characteristics.